Thyroid hormone membrane receptor binding and transcriptional regulation in the sea urchin Strongylocentrotus purpuratus - Taylor, Elias; Wynen, Hannah; Heyland, Andreas (Frontiers in Endocrinology, 2023)
Thyroid hormones (THs) are small amino acid derived signaling molecules with broad physiological and developmental functions in animals. Specifically, their function in metamorphic development, ion regulation, angiogenesis and many others have been studied in detail in mammals and some other vertebrates. Despite extensive reports showing pharmacological responses of invertebrate species to THs, little is known about TH signaling mechanisms outside of vertebrates. Previous work in sea urchins suggests that non-genomic mechanisms are activated by TH ligands. Here we show that several THs bind to sea urchin (Strongylocentrotus purpuratus) cell membrane extracts and are displaced by ligands of RGD-binding integrins. A transcriptional analysis across sea urchin developmental stages shows activation of genomic and non-genomic pathways in response to TH exposure, suggesting that both pathways are activated by THs in sea urchin embryos and larvae. We also provide evidence associating TH regulation of gene expression with TH response elements in the genome. In ontogeny, we found more differentially expressed genes in older larvae compared to gastrula stages. In contrast to gastrula stages, the acceleration of skeletogenesis by thyroxine in older larvae is not fully inhibited by competitive ligands or inhibitors of the integrin membrane receptor pathway, suggesting that THs likely activate multiple pathways. Our data confirms a signaling function of THs in sea urchin development and suggests that both genomic and non-genomic mechanisms play a role, with genomic signaling being more prominent during later stages of larval development.